Combinations of physical activity, screen time and sleep, and their association with subjective wellbeing in children. (May 2023) - Sun, Jiangang; Jiang, Xiaoran; Wei, Shanshan
Abstract: Background: Subjective wellbeing is an important indicator of health outcomes in children. 24-hour movement behaviours (i.e., physical activity, sedentary behaviour, sleep and their combination), a set of modifiable lifestyle behaviours, have been demonstrated to be associated with subjective wellbeing. Thus, the aim of this study was to investigate the relationship between the compliance of the 24-h movement guidelines and subjective wellbeing in a sample of Chinese children. Methods: Cross-sectional data from primary and secondary school students in Anhui Province, China were used for the analysis. A total of 1098 study participants (mean age: 11.6 years, body mass index: 19.7 ± 2.9) were included, of which 51.5% were boys. Physical activity, screen time, sleep, and subjective wellbeing were measured using validated self-reported questionnaires. Multivariable logistic regression analysis was used to assess the relationships between the compliance of different combinations of 24-h movement guidelines and subjective wellbeing in participants. Results: The compliance of (i.e., physical activity recommendations, screen time recommendations and sleep recommendations) 24-h movement guidelines was associated with better subjective wellbeing (OR: 2.09; 95CI%: 1.01–5.90) compared to the compliance of none of the guidelines. Furthermore, there was a dose–response relationship between the number of guidelines met (3 > 2 > 1 > 0) and improved subjective wellbeing ( p  < 0.05). Despite some exceptions, there was a significant relationship between the compliance of different combinations of the guidelines and better subjective wellbeing. Conclusion: This study found that the compliance of 24-h movement guidelines was associated with greater subjective wellbeing in Chinese children. Highlights: Adherence to the 24-h movement guidelines may lead to better subjective wellbeing in children. Promoting optimal healthy movement behaviours is associated with improved mental health in children. Encouraging children to have more healthy movement behaviours is essnetial for better subjective wellbeing.